Theoretical and methodological study of the problems of observation the state of the national economic system and analysis of the national economic system - Verigo, Anastasiya V. (Journal of the Belarusian State University. Economics, 2025)
This article explores the challenges of systems research in complex, nonlinear, dynamic systems undergoing various transformations (natural evolution, bifurcations, crises, and various external influences) – the problems of observation and analysing the national economic system. Contemporary economic literature has extensively explored the structure, analysis, and management of national economic systems. However, assessing the functioning of the national economy as it moves remains insufficiently addressed. This article draws on the work of contemporary scholars in management theory and the theoretical foundations of systems research. The application of these works, through the lens of modern economic theory, has enabled us to substantiate and develop the stages of a structural and logical representation of the challenges of observation of the state of the national economic system and analysing the national economic system as a dynamic, multi-connected, multi-parameter structure. The developed algorithm allows us to take into account the main difficulties of observation the state of nonlinear, dynamic, multi-connected, multi-parameter systems and analysing the national economic system in the context of constructing econometric models for managing macroeconomic processes, including three control loops (the primary control loop, the disturbance-management loop, and the self-adjustment loop).
Keywords: system research; theory of systems; national economic system; observation of the state of the national economic system and analysis of the national economic system; management of the national economy